(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Video data are being compressed and distributed using one of several coding standards, among which the most recent and popular is the High Efficiency Video Coding (HEVC) standard. The threatening growth of security attacks, on the other hand, has brought security and privacy concerns to the attention of governments and people as well. In the absence of a reliable security system, shared multimedia data used on the public networks such as the internet will continue to be exposed to different types of attacks, making end-to-end encryption for video data a necessity to protect their sensitive information. Therefore, providing a reliable video security technique that complies to and fulfills the requirements of HEVC is pertinent. In this paper, a fast selective encryption approach is developed to provide protection for video bitstreams of HEVC, which can be used in real-time video applications, with low computational overhead and maintaining the standard’s video bit rate. This approach employs the popular Advance Encryption Standard (AES) algorithm to encrypt selected elements in the horizontal intra prediction modes. Experimental evaluations confirm the provision of adequate security level of video information, with no bitrate increase, no increase in computational delay and no additional impact on the compression performance when compared to non-secure techniques, while also achieving a satisfactory trade-off between the encryption reliability, flexibility, and computational complexity. The security level of this method was found to be strongly secure against plaintext and brute force attacks.